Striatal molecular alterations in HD gene carriers: a systematic review and meta-analysis of PET studies - Niccolini, Flavia; Pagano, Gennaro; Fusar-Poli, Paolo; Wood, Andrew; Mrzljak, Ladislav; Sampaio, Cristina; Politis, Marios (Journal of neurology, neurosurgery and psychiatry, 2018)
BackgroundOver the past years, positron emission tomography (PET) imaging studies have investigated striatal molecular changes in premanifest and manifest Huntington’s disease (HD) gene expansion carriers (HDGECs), but they have yielded inconsistent results.ObjectiveTo systematically examine the evidence of striatal molecular alterations in manifest and premanifest HDGECs as measured by PET imaging studies.MethodsMEDLINE, ISI Web of Science, Cochrane Library and Scopus databases were searched for articles published until 7 June 2017 that included PET studies in manifest and premanifest HDGECs. Meta-analyses were conducted with random effect models, and heterogeneity was addressed with I2 index, controlling for publication bias and quality of study. The primary outcome was the standardised mean difference (SMD) of PET uptakes in the whole striatum, caudate and putamen in manifest and premanifest HDGECs compared with healthy controls (HCs).ResultsTwenty-four out of 63 PET studies in premanifest (n=158) and manifest (n=191) HDGECs and HCs (n=333) were included in the meta-analysis. Premanifest and manifest HDGECs showed significant decreases in dopamine D2 receptors in caudate (SMD=−1.233, 95% CI −1.753 to −0.713, p<0.0001; SMD=−5.792, 95% CI −7.695 to −3.890, p<0.0001) and putamen (SMD=−1.479, 95% CI −1.965 to −0.992, p<0.0001; SMD=−5.053, 95% CI −6.558 to −3.549, p<0.0001), in glucose metabolism in caudate (SMD=−0.758, 95% CI −1.139 to −0.376, p<0.0001; SMD=−3.738, 95% CI −4.880 to −2.597, p<0.0001) and putamen (SMD=−2.462, 95% CI −4.208 to −0.717, p=0.006; SMD=−1.650, 95% CI −2.842 to −0.458, p<0.001) and in striatal PDE10A binding (SMD=−1.663, 95% CI −2.603 to −0.723, p=0.001; SMD=−2.445, 95% CI −3.371 to −1.519, p<0.001).ConclusionsPET imaging has the potential to detect striatal molecular changes even at the early premanifest stage of HD, which are relevant to the neuropathological mechanisms underlying the development of the disease.